Ozone Oxidation of Kraft Bamboo Pulp for Preparation of Nanofibrillated Cellulose - Mingyou Liu; Xia Chen; Xiaofei Tian (International Journal of Polymer Science)
The influence of ozonation on the homogenization of Kraft bamboo pulp (KBP) for the production of nanofibrillated cellulose (NFC) was studied. Using optimized conditions for ozonation, that is, pulp consistency 35%, ozone dosage 0.87% (v/w), and pH=2.5, the kappa number and viscosity of KBP decreased from 10.8 to 2.8 and from 1024 mL∙g−1 to 258 mL∙g−1, respectively, while the crystallinity and carboxylate content increased from 36.2% to 48% and 0.93 mmol/g to 1.26 mmol/g, respectively. The ozonation-treated KPB was used as the substrate for NFC preparation through homogenization. With a width of 10–20 nm and length≥250 nm, the prepared NFC had a high aspect ratio of length versus width. Ozonation can be used as an alternative approach to promote the efficient production of NFC from KBP.